Gastric Duplication: A Rare Cause of Recurrent Vomiting - Brahmananda Koduri; Katie McHale; Christina Yost; Michael H. Goodman; Dennis Hoelzer (Case Reports in Pediatrics)
Vomiting is a physical finding that can occur at any age but presents the greatest challenge when it is recurrent in a child. The etiology is varied (Sieunarine and Manmohansingh, 1989; Suzuki, 1982), and recurrent vomiting can be a symptom of life threatening medical or surgical emergencies. Early recognition is mandatory for preventing delay in management and potential complications. Gastric duplication is rare and mostly diagnosed in infancy with only a few cases documented in the medical literature presenting in childhood. We present a three-year-old Vietnamese female with recurrent vomiting. Obstruction and sepsis were ruled out as a cause of the recurrent vomiting by history and appropriate tests. Persistent vomiting and paucity of air on the plain abdominal films provided a clue to the diagnosis. A CT scan of the abdomen with contrast revealed a uniformly thin walled fluid attenuation mass in the epigastric region which did not opacify with contrast. An abdominal ultrasound confirmed gastric duplication cyst and the patient was taken to the operating room for excision of the cyst.